Meningkatkan Kemampuan Penalaran Dan Disposisi Matematis Siswa SMP Melalui Pendekatan Metaphorical Thinking - Widyasari, Nurbaiti; Dahlan, Jarnawi Afgani; Dewanto, Stanley (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
The aim of this research are examining to improve student’s mathematical reasoning and disposition by metaphorical thinking approach. The research utilized a quasi experimental design. The population in this research are students in grade eight from one of junior high school in East Jakarta. As concern, the sample was 27 students in VIII-3 class for control group, and 31 students in VIII-5 class for experiment group. The instruments comprised of mathematical reasoning test and disposition scale. The quantitative analysis is used a two-way ANOVA, while qualitative analysis used a descriptive one. The result of qualitative analysis shows the students were able to metaphors a concept and also able to make connection between concepts. Futhermore, the result of quantitative analysis shows better increasing mathematical reasoning ability by metaphorical thinking approach than by conventional teaching, while there was no different increment in mathematical disposotion between two classes. There was no interaction effect between student’s prior mathematics ability and teaching approach toward student’s mathematical reasoning and disposition.